THE ANATOMY OF POST-TOTALITARIANISM. - Michał Kwiecień, Michał Kwiecień (Porównania, 2019)
The purpose of this article is to critically analyze the main theses of Aviezer Tucker’s book The Legacies of Totalitarianism. A Theoretical Framework. Tucker’s views on the political transformation in Central and Eastern Europe are confronted with conclusions of Janine J. Wedel, Andrzej Zybertowicz and Krzysztof Brzechczyn.